Combining ability for kernel yield and its component traits in groundnut (Arachis hypogaea L.): COMBINING ABILITY FOR KERNEL YIELD AND ITS COMPONENT TRAITS IN GROUNDNUT - A MOTHILAL,; M JAYARAMACHANDRAN, (Journal of Oilseeds Research, 2014)
Combing ability was estimated among eight parents for yield and its contributing traits in groundnut. Both per se performance and gca effects were considered for judging the genotype as best parent. The Virginia bunch genotype GG 21 and Spanish bunch genotypes TMV Gn 13 and VRI Gn 6 recorded significant gca effect for kernel yield, pod yield, number of mature pods and number of primaries. Hence, these genotypes were categorized as good combiners. The cross GG 21 x VRI Gn 6 registered significant sca effect for kernel yield, pod yield, number of mature pods and plant height; while VG 104 x VRI 3 recorded significant sca effect for kernel yield, pod yield, number of mature pods, number of secondaries and number of primaries. The former cross involves parents with good combiners. Hence, pedigree breeding method could be adopted to isolate desirable recombinants. However, the later cross involved parents with poor combiners. Hence, biparental mating followed by selection isrecommended for the identification of desirable recombinants.